Literasi Digital pada Siswa MTs Darussalam Kota Bengkulu Upaya Meningkatkan Pengetahuan tentang Kekerasan Seksual dalam Perspektif Islam - Poppi Damayanti; Yuhaswita Yuhaswita (Yayasan Darussalam Bengkulu, 2026)
This Community Service is designed with a training design with the aim of increasing the knowledge of MTs Darussalam students about sexual violence in an Islamic perspective, as one of a series of Community Service from Fatmawati Sukarno State Islamic University Bengkulu. Held on November 2, 2024 at the MTs Darussalam class hall in Bengkulu City, with 30 participants consisting of representatives from grades 7 to 9. Facilitated by two lecturers from Fatmawati Sukarno State Islamic University Bengkulu and assisted by two students of Islamic Communication and Broadcasting from Fatmawati Sukarno State Islamic University Bengkulu. The implementation began with participant registration, opening of the event, pre-test, provision of material, continued with a question and answer session or discussion, and ended with a photo and meal together.